2003
DOI: 10.1038/sj.bjc.6601220
|View full text |Cite
|
Sign up to set email alerts
|

Are smoking and chlamydial infection risk factors for CIN? Different results after adjustment for HPV DNA and antibodies

Abstract: To identify the risk factors for cervical intraepithelial neoplasia (CIN), we reanalysed the data from our previous case -control study by adjusting for human papillomavirus (HPV) antibodies. Unlike our previous study based only on HPV DNA, smoking and Chlamydia trachomatis infection were revealed as significant risk factors for CIN after adjustment for HPV antibodies. Infections by oncogenic human papillomaviruses (HPVs) are established as a major risk factor for cervical intraepithelial neoplasia (CIN) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
1
11
2
Order By: Relevance
“…Moreover, most of the research reported on the association smoking and high-grade CIN mainly. The report of Matsumoto et al included CIN1, but did not divide CINs [46]. One of possibilities about this discrepancy is that the ratio of non-smoker was quite higher ranged from 82.0% to 89.8% in four different groups due to the cultural reason in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, most of the research reported on the association smoking and high-grade CIN mainly. The report of Matsumoto et al included CIN1, but did not divide CINs [46]. One of possibilities about this discrepancy is that the ratio of non-smoker was quite higher ranged from 82.0% to 89.8% in four different groups due to the cultural reason in our study.…”
Section: Discussioncontrasting
confidence: 53%
“…This observation contrasts that of Schlecht et al39 An earlier study reported that daily cigarette smoking had a deleterious effect and contributed to development of low-grade squamous intraepithelial lesions 43. Several epidemiologic studies have identified a role of cigarette smoking in invasive cervical cancer 26,27,44. Nicotine and other cigarette metabolites have been found in cervical mucus 45.…”
Section: Discussionmentioning
confidence: 85%
“…This could have implications for studies investigating co-factors influencing progression of HPV-infected cells to precancer and cancer, whereby associations found could be due to residual confounding by HPV positivity. As an example, some studies that have found an association between Chlamydia trachomatis (Ct) and cervical cancer, in the absence of HPV DNA exposure, have used HPV serology to account or adjust for HPV status (1921). Based on our results, given that they used an assay with similar misclassification of HPV exposure as the one we evaluated in this report, 25% of HPV16 and 48% of HPV18 exposed women would be classified as HPV-negative.…”
Section: Discussionmentioning
confidence: 99%